(untitled) (The Journal of Psychology and Sociology, 2025)
In the digital age, media escapism has become an integral part of everyday life, often serving as a means of coping with stress. This study aims to investigate the relationship between stress levels and digital escapism, examining how individuals use digital media to regulate emotional states. The research highlights the psychological and practical significance of understanding digital escapism as a coping mechanism. By identifying the extent to which stress influences media consumption patterns, this study contributes to the broader discussion on mental health and digital behavior. The methodology includes a quantitative approach, utilizing validated psychological scales to assess stress levels and media escapism tendencies among participants. Statistical analysis was applied to determine correlations between these variables. The findings suggest a significant relationship between stress and media escapism, indicating that higher stress levels may lead to increased engagement in digital content as a form of psychological relief. These results contribute to the growing body of knowledge on digital psychology, offering insights into the potential risks and benefits of media escapism in stress management. The practical implications of this study lie in its relevance for psychologists, educators, and policymakers seeking to develop strategies for healthier digital consumption habits. Understanding the role of digital escapism in stress regulation can inform interventions aimed at promoting psychological wellbeing in the digital era. Keywords: digital escapism, stress, media consumption, psychological well-being.